Mouthpart morphology of six freshwater species of Cymothoidae (Isopoda) from Amazonian fish compared to that of three marine forms, with the proposal of Artystonenae subfam. nov. - Thatcher, Vernon E. (Amazoniana, 1997)
The mouthpart morphology of six Arnazonian freshwater species of Cymothoidae (Isopoda) was compared to that of three marine forms. The freshwater species were: Braga cichlae SCHIODTE & MEINERT.
Keywords: Cymothoidae